Operational Method of Stem Turbine Installation under Non-Conventional Modes - V. P. Kashcheev; E. O. Vоrоnоv; V. A. Khаimоv; A. V. Kashcheev; V. N. Sоrоkin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2011)
While starting turbines from cold and non-cooled-down states rotors are heated quicker than cylinders due to significantly less weight and more intensive interaction with steam and the value of their differential expansion reaches up to the rated ones in the period of 4-5 hours.The investigations have revealed that while using a swirling steam attemperator it is possible to feed steam to turbine seals of the required temperature and at the required time during its variable operational conditions. This methodology makes it possible to save 400 t of specific fuel. In addition to this operational reliability of a power block is increased and a number and cost of repairs is decreased.